2009
DOI: 10.5194/adgeo-22-73-2009
|View full text |Cite
|
Sign up to set email alerts
|

Large scale features associated with strong frontogenesis in equivalent potential temperature in the South American subtropics east of the Andes

Abstract: South American subtropics east of the Andes exhibit a region of intense climatological frontogenesis in equivalent potential temperature (EPT) in the December to March season, mostly produced by deformation of the wind field. The goal of this paper is to investigate the large scale features associated with intense and weak frontogenesis by deformation (FGD) in EPT in the region where it attains its climatological maximum. This can be approximately delimited by 32–42° S and 66–69° W, which is sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…The composites identify northward propagating frontal systems and the associated low-pressure anomalies as common drivers of extreme rainfall in SESA and the establishment of a low-level wind channel from the Amazon to the subtropics: a low-pressure anomaly originating from Rossby-wave activity propagates northwards, led by a cold front causing abundant rainfall in SESA through the uplifting of warmer air masses 9,10,30,31 . When the frontal system propagates from SESA northeastward through the La Plata Basin in northeastern Argentina, the low-pressure anomaly extends to central Bolivia and merges with the Northwestern Argentinean Low 4,12 (Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composites identify northward propagating frontal systems and the associated low-pressure anomalies as common drivers of extreme rainfall in SESA and the establishment of a low-level wind channel from the Amazon to the subtropics: a low-pressure anomaly originating from Rossby-wave activity propagates northwards, led by a cold front causing abundant rainfall in SESA through the uplifting of warmer air masses 9,10,30,31 . When the frontal system propagates from SESA northeastward through the La Plata Basin in northeastern Argentina, the low-pressure anomaly extends to central Bolivia and merges with the Northwestern Argentinean Low 4,12 (Fig. 3a).…”
Section: Resultsmentioning
confidence: 99%
“…The cause of the circulation variability and the corresponding rainfall anomalies has not yet been identified in a way that sufficiently resolves the temporal order of events [9][10][11][12] . Since this is crucial for predicting associated extreme rainfall events, an early warning system for extreme rainfall in the ECA has been lacking.…”
mentioning
confidence: 99%
“…The number of these events is similar throughout the day, with a slightly higher number of events during the afternoon and evening (1800 and 0000 UTC). The summer month's maximum number of q-gradient events is highly coincident with the region of maximum mean frontogenesis at 850 hPa identified by Arraut and Barbosa (2009). They showed that deformation frontogenesis was the primary source of this maximum.…”
Section: A Annual Cycle and Geographical Distribution Of Drylinesmentioning
confidence: 76%
“…The authors state that disturbances in the middle or exit regions of the storm track tend to develop due to the ageostrophic fluxes convergence, while the disturbances at the entrance region of the storm tracks grow by baroclinic conversion. This seems to be the case of the K2 and K3, because K2 maximum develops (with AFC term important) at the end of the Pacific Storm track and the K3 maximum develops over the South America (in the beginning of Atlantic Storm tracks) region known to be frontogenetic (Satyamurty and Mattos, ; Arraut and Barbosa, ).…”
Section: Discussionmentioning
confidence: 99%